Status Penguasaan Tanah Pasca Berakhirnya Hak Guna Bangunan Dalam Perjanjian Jual Beli Antara Masyarakat Dan Perseroan Terbatas - Amrudin Yakseb (Al-Mizan: Jurnal Kajian Hukum dan Ekonomi, 2025)
This study aims to analyze the status of land possession after the expiration of Building Use Rights (HGB) in the sale and purchase agreement between the public and limited liability companies (PT). The research method employed is normative legal research with an approach to regulations, legal doctrines, and relevant jurisprudence regarding HGB. The main finding reveals that after the expiration of HGB, the land legally reverts to state ownership, while the buyer only possesses the building without legal entitlement to the land. Sale and purchase agreements that do not include clear information regarding the duration of HGB lead to legal uncertainty for the buyers. This study contributes by providing recommendations for legal protection for buyers and enhancing transparency in HGB-related land transactions. The practical contribution of this research is to strengthen preventive legal protection and improve public understanding of the legal status of land in HGB sale agreements.